Mechanism of photoreceptor cGMP phosphodiesterase inhibition by its gamma-subunits. - Artemyev, N O (1996)
cGMP phosphodiesterase (PDE) is the key effector enzyme of vertebrate photoreceptor cells that regulates the level of the second messenger, cGMP. PDE consists of catalytic alpha and beta subunits (Palpha and Pbeta) and two inhibitory gamma subunits (Pgamma) that block PDE activity in the dark. The major inhibitory region has been localized to the C terminus of Pgamma. The last C-terminal residues -IleIle form an important hydrophobic domain critical for the inhibition of PDE activity. In this study, mutants of Pgamma were designed for cross-linking experiments to identify regions on Palpha and Pbeta subunits that bind to the Pgamma C terminus. In one of the mutants, the cysteine at position 68 was substituted with serine, and the last four C-terminal residues of Pgamma were replaced with a single cysteine. This mutant, Pgamma83Cys, was labeled with photoprobe 4-(N-maleimido) benzophenone (MBP) at the cysteine residue. The labeled Pgamma83CysMBP mutant was a more potent inhibitor of PDE activity than the unlabeled mutant, indicating that the hydrophobic MBP probe mimics the Pgamma hydrophobic C terminus. A specific, high-yield cross-linking of up to 70% was achieved between the Pgamma83CysMBP and PDE catalytic subunits. Palpha and the N-terminally truncated Pbeta (lacking 147 aa residues) cross-linked to Pgamma83CysMBP with the same efficiency. Using mass spectrometric analysis of tryptic fragments from the cross-linked PDE, we identified the site of cross-linking to aa residues 751-763 of Palpha. The corresponding region of Pbeta, Pbeta-749-761, also may bind to the Pgamma C terminus. Our data suggest that Pgamma blocks PDE activity through the binding to the catalytic site of PDE, near the NKXD motif, a consensus sequence for interaction with the guanine ring of cGMP.